Pengaruh Kompetensi Sumber Daya Manusia Dan Motivasi Terhadap Kinerja UMKM Sektor Kuliner Di Kecamatan Payung Sekaki di Kota Pekanbaru Dengan Dukungan Pemerintah Sebagai Variabel Moderasi - Ananda, Salsabilla; Lestari Garnasih, Raden; Fitri , Kurniawaty (Bahtera Inovasi, 2024)
This research aims to determine the influence of Human Resource Competency and Motivation on the Performance of Culinary MSMEs in Payung Sekaki sub-district with Government Support as moderating variable. The population in this study was culinary MSMEs located in the Payung Sekaki sub-district, Pekanbaru City, totaling 705 people. By using the Slovin formula, the number of samples used in this research was 88 respondents. The data collection technique uses a questionnaire distribution method, to test the hypothesis in this research using Structural Equation Modeling - Partial Least Square (SEM-PLS) with the help of the SmartPLS 3.0 program. The sampling technique was carried out using a purposive sampling method and 88 owners were selected as samples. The results of this research show that: 1) There is a positive and significant influence between Human Resource Competence on the Performance of Culinary MSMEs, 2) There is a positive and significant influence between Motivation on the Performance of Culinary MSMEs, 3) There is no significant influence between Human Resource Competence on Performance of Culinary MSMEs moderated by Government Support, 4) There is no significant influence between Motivaton on the Performance of Culinary MSMEs moderated by Government Support.